ANALISIS KUALITAS PADA PRODUKSI LABELSTOCK KERTAS HVS DI PT â€œXâ€ - Purtomo, Tjahjo (Heuristic, 2014)
PT. "X" one of the manufacturing industry engaged in the manufacture of paper labels,release liner and packaging tape, and while also receiving another product label orders. Theprocess of coating on this company using wet glue placed on release paper is then dried using adryer, so that the glue dries quickly, and then combined with certain items. In order toguarantee the quality of products, the company implemented a control chart X and R are used tomeasure the uniformity of the thickness of the glue on all sides, and the cause and effectdiagram is used to infer the cause of the difference in the thickness of the glue on labelstockproduction.With the above method, the obtained results that the Lower Control Limit 20 LimitControl Over 22, and the target of 21. Cp value of 0.19 (Cp < 1) means that the process is notcapable. While the resulting Cpk value of 0.05 (Cpk< 1), we conclude that the thickness of theglue is not capable or not of accuracy and precision. The cause of differences in the thickness ofthe glue is supposedly 5 factors, namely human factors, raw materials, machines, methods andenvironment. The cause of differences in the thickness of the glue is supposedly 5 factors,namely human factors, raw materials, machines, methods and environment.Kata kunci : Pengendalian Kualitas, Labelstock